2005
DOI: 10.1051/0004-6361:20053454
|View full text |Cite
|
Sign up to set email alerts
|

Active longitudes, nonaxisymmetric dynamos and phase mixing

Abstract: We discuss the problem of solar active longitudes from the viewpoint of dynamo theory. We start from a recent observational analysis of the problem undertaken by Berdyugina & Usoskin (2003, A&A, 405, 1121 and Usoskin et al. (2005, A&A, 441, 347) who demonstrated from a study of sunspot data that solar active longitudes rotate differentially, with a small but significant asynchrony between northern and southern hemispheres. We suggest two concepts by which the underlying magnetic structure could lead to the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 49 publications
9
48
1
Order By: Relevance
“…This result was doubted by Pelt et al (2005). After refining their methods, Usoskin et al (2005) and Berdyugina et al (2006) confirmed the previous result. Usoskin et al (2005) introduced a dynamic reference frame which rotates with the mean rate of the differential rotation with respect to the phase of the solar cycle.…”
Section: Introductionsupporting
confidence: 71%
“…This result was doubted by Pelt et al (2005). After refining their methods, Usoskin et al (2005) and Berdyugina et al (2006) confirmed the previous result. Usoskin et al (2005) introduced a dynamic reference frame which rotates with the mean rate of the differential rotation with respect to the phase of the solar cycle.…”
Section: Introductionsupporting
confidence: 71%
“…Berdyugina et al (2006) and Usoskin et al (2007) summarized the dynamo modes related to the occurrence of preferred longitudes in solar and stellar activity and discussed the interpretation of the existence of active longitudes within several solar dynamo related and other scenarios (see also Ruzmaikin 1998;Rädler et al 1990;Moss 1999Moss , 2004Mason et al 2002;Fluri & Berdyugina 2005;Bassom et al 2005;Korhonen & Elstner 2005). Berdyugina et al (2006) noted that in most dynamo models the generated structures are expected to rotate quasirigidly, while the migration of active longitudes could be caused by a stroboscopic effect. Nevertheless, the significantly varying rate of asymmetry and rotation from one cycle to another, as well as the significant hemispheric differences provide observational constraints that need to be taken into account in dynamo modeling.…”
Section: Discussionmentioning
confidence: 99%
“…This would mean that these active longitudes are related to internal changes, such as the dynamo mechanisms occurring inside the star. In particular this has been studied theoretically with dynamo models (Berdyugina et al 2006;Weber et al 2013). …”
Section: Long-lived Featuresmentioning
confidence: 99%